2015
DOI: 10.4085/1062-6050-50.5.06
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Enhanced Eversion Force Sense in Ankles With or Without Functional Instability

Abstract: Context: Force sense impairments are associated with functional ankle instability. Stochastic resonance stimulation (SRS) may have implications for correcting these force sense deficits.Objective: To determine if SRS improved force sense. Design: Case-control study. Setting: Research laboratory.Patients or Other Participants: Twelve people with functional ankle instability (age ¼ 23 6 3 years, height ¼ 174 6 8 cm, mass ¼ 69 6 10 kg) and 12 people with stable ankles (age ¼ 22 6 2 years, height ¼ 170 6 7 cm, mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Further studies are necessary to increase knowledge of changes that occur in the peroneus muscles and connective tissues of participants with LAS. Postural control strategies, 37 the neural excitability of the lower extremities, 38 changes in the eversion force sense in ankles with functional instability, 39 and corticospinal excitability at the ankle joint 40 are some of the conditions related to the muscle and connective tissue changes observed in patients with LAS.…”
Section: Future Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies are necessary to increase knowledge of changes that occur in the peroneus muscles and connective tissues of participants with LAS. Postural control strategies, 37 the neural excitability of the lower extremities, 38 changes in the eversion force sense in ankles with functional instability, 39 and corticospinal excitability at the ankle joint 40 are some of the conditions related to the muscle and connective tissue changes observed in patients with LAS.…”
Section: Future Studiesmentioning
confidence: 99%
“…One of the main limitations of this study was the lack of distinction between participants with chronic ankle instability and those with functional ankle instability. 38,39 Neuromuscular dysfunction of the fibularis longus muscle, including greater inhibition of corticospinal excitability, is frequently observed in those with chronic ankle instability. 38 Force sense impairments are also correlated with functional ankle instability.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have found that patients with CAI might have impaired ankle force sense, 14,15 there have also been some studies that did not find significant associations. 12,16 Potential reasons for these inconsistent findings might include both small sample sizes and differences in test methodologies. 12 The force reproduction test (also called the force matching test) is the most common approach to measuring force sense.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 41 women, 18 without SUI and 23 with SUI (mean ages 46.7 (SD 3.04) and 51.5 (1.86) years, respectively) were included (26,27). The demographic characteristics of the participants are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%